The production and composition of Chinese lead-barium glass through experimental laboratory replication - Ma, Qian; Braekmans, Dennis; Shortland, Andrew J.; Pollard, A. Mark (Elsevier, 2020)
Lead-barium glass appeared during the late Warring States period in China (457 - 221 BCE) and was considered as a Chinese invention due to the unique presence of high barium. There is no indication as to how it was made. A set of twenty-four different combinations of possible raw materials were melted to test and systematically evaluate the possible recipes for lead-barium glass. Specifically, the function and source of sodium in lead-barium glass were explored. The results show that sodium source is crucial for lead-barium glass forming in this particular system. This paper explores an alternative formulation since sodium flux is not reported in historical Chinese sources, in which the Na2O is provided by including soda-lime glass in the mixture. This particular formulation provides a potential explanation for the source of the sodium in lead-barium glass
Keywords: Chinese glass; Opacifier; Sodium; Crucibles; Lead-barium glass